From literary girl to graphic novel hero — transmedial transformation of Stieg Larsson’s Lisbeth Salander - Bergman, Kerstin (The Journal of Specialised Translation, 2014)
Stieg Larsson's Millennium Trilogy (2005–2007) has become an international hyper-bestseller phenomenon, translated and adapted across linguistic, cultural, and medial boundaries. But what happens to Larsson's complex woman protagonist, Lisbeth Salander, when the story is adapted and transformed? In this article, Larsson's first novel, The Girl with the Dragon Tattoo (2005), is compared to its graphic novel adaptation (2012–2013), written by Denise Mina with visual renderings by Leonardo Manco and Andrea Mutti. The transformation of Salander is analysed by means of comparative close readings of central scenes, and media specific features in combination with additional choices made by the creators of the graphic novel are highlighted. It is concluded that in the graphic novel, Salander is depicted as more "normal" and simultaneously more of an outcast, less of a (feminist) superhero, softer and more emotional, and less of an expression of feminism than she is in Larsson's novel. Mina, Manco, and Mutti are found to contribute to transforming Salander in a manner that weakens the strong political agenda that characterised Larsson's original novel.